Isidro Vanegas, ed. El siglo diecinueve colombiano. (2018)
Political history was fairly recently seen as a moribund field, the study of machinations among elites that had little connection to culture and society. Over the past couple of decades, however, political history has transformed itself by focusing on larger issues of the culture of politics and by incorporating the experience and agency of subalterns into the story of state and nation formation. This valuable volume of eight essays and an introduction reveals how much political history has changed and how these changes have revolutionized our understanding of the nineteenth century. For a collection of essays, the volume is unusually coherent in its themes, the essays as a whole sustaining an argument about the vibrancy and inventiveness of Colombian nineteenthcentury political culture. As Isidro Vanegas notes in his excellent introduction, the Colombian nineteenth century has long been seen as a failure, both in nation and state building. However, this sense of failure and stagnation was not the view of many in Colombia during the nineteenth century, especially before the Regeneration. Instead, many politicians, letrados, and even everyday people (Liberals especially, but also some Conservatives), saw Colombia as a political success in comparison with Europe and the United States.